Analisis Peramalan Penjualan Jasa Freight Forwarding pada PT. Camar Cargo Logistics - Annisa Putri Yudhita; Heri Ribut Yuliantoro; Tobi Arfan (Politeknik Caltex Riau, 2016)
This research is intended to find out more about how to forecast and to find out how many is the total sales of freight forwarding service for export and import in PT. Camar Cargo Logistics. For this research, the author is using autoregretion and autocorrelation method. The results from this research are : (1) The sales forecast of freight forwarding service for export each semester from the period of 2016 until 2018 are 124.208, 123.098, 121.880, 120.544, 119.078, 117.471. (2) The sales forecast of freight forwarding service for import each semester from the period of 2016 until 2018 are 48.908, 46.853, 44.448, 41.634, 38.342, 34.490. (3) According to the calculation of MSE (Mean Squared Error) and MAE (Mean Absolute Error), autoregression and autocorrelation method are the best methods for sales forecasting if they are compared to single exponential smoothing method. The conclusion from this research is sales forecast from freight forwarding service for export and for import is decreasing each semester from the period of 2016 until 2018.